Keberhasilan Sistem Ekonomi yang Mengeluarkan Swedia dari Krisis Akibat Perang Dunia 1 - Azizah Ratu Felita Abduh; Nadhira Zahra Aulia Putri; Vianna Antoneta Putri; Muthia Nugraha (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
World War I was a global war that involved various countries in Europe along with Russia, the United States, the Middle East, and other regions. World War I was one of the turning points in the geopolitical history of the 20th century. The war led to the fall of four major imperial dynasties (in Germany, Russia, Austria-Hungary, and Turkey), which not only harmed the countries that participated in the war, but also other countries such as Sweden. Sweden made various efforts to keep its country afloat in a precarious situation. This article will explain how Sweden emerged from the economic crisis caused by World War I to become a prosperous country.